Relatório de estágio curricular supervisionado em medicina veterinária - área de patologia veterinária - (:unkn) unknown (Universidade Federal do Pampa, 2015)
The Supervised Curricular Internship in Veterinary Medicine (ECSMV) was carried out in the area of ​​Veterinary Pathology, at the Animal Pathology Laboratory (LAPA) of the University of the State of Santa Catarina (UDESC), Campus of Agroveterinary Sciences (CAV), between 02 from March to June 12, 2015 in the city of Lages. LAPA performs diagnoses of domestic and wild animals, with the aid of necropsies and histopathology. The ECSMV comprised a total of 560 hours and a workload of 40 hours per week, which allowed the monitoring of laboratory routine, theoretical and practical classes of pathology and toxicology and development of graduate projects. In total, 126 necropsies and 267 histopathological examinations were followed. Among the species evaluated at necropsies, 59 canines, 25 bovines, 20 felines, eight chickens, five sheep, five horses, two wild animals, one pig and one lagomorph. From the materials received for histopathology, 156 dogs, 61 cattle, 23 cats, 15 chickens, six sheep, four pigs and two horses were evaluated. There were also 19 field trips, in municipalities in the state of Santa Catarina, with the objective of epidemiological investigation, necropsies and collections of toxic plants. Among the cases monitored, cases of rabies were described in cattle in the southern region of Santa Catarina, cases of isolated deaths caused by acute poisoning by Pteridium arachnoideum in a cattle, poisoning by Cestrum corymbosum var. hirsutum in a bovine and a case of feline toxoplasmosis. The diagnoses were made through an epidemiological study, together with clinical and pathological findings.
Report of supervised internship report on veterinary medicine - veterinary pathology
Keywords: Medicina veterinária; Veterinary medicine; Patologia veterinária; Veterinary pathology; CNPQ::CIENCIAS AGRARIAS